The new renaissance of family medicine: Myth or reality - Homar Vesna; Švab Igor (Sciendo, 2023)
Renaissance is the term used for the societal movement that marked the end of the Middle Ages. With the development of science came the rediscovery of the works and values of ancient scholars. This brought enormous development in all areas of society, including education. Man became the measure of all things, humanism became important again, and there was a blossoming of science and art.